2020
DOI: 10.1371/journal.pone.0234313
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the bacterial ocular surface microbiome in ophthalmologically normal dogs prior to and following treatment with topical neomycin-polymyxin-bacitracin

Abstract: The ocular surface microbiome of veterinary species has not been thoroughly characterized using molecular-based techniques, such as next generation sequencing (NGS), as the vast majority of studies have utilized traditional culture-based techniques. To date, there is one pilot study evaluating the ocular surface of healthy dogs using NGS. Furthermore, alterations in the ocular surface microbiome over time and after topical antibiotic treatment are unknown. The objectives of this study were to describe the bact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 46 publications
3
29
0
Order By: Relevance
“…In fact, diagnostic tests other than culture-based methods will soon become the gold standard for microbial species identification as the field of clinical microbiology is rapidly evolving. Unlike culture-based methods, technologies such as mass spectrometry and nucleic acid sequencing provide rapid and sensitive tools to probe the microbiome in clinical patients ( 39 )—as recently described for the ocular surface of veterinary species ( 40 , 41 )—enabling clinicians to optimize the antibiotic treatment sooner and thereby improve clinical outcomes ( 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, diagnostic tests other than culture-based methods will soon become the gold standard for microbial species identification as the field of clinical microbiology is rapidly evolving. Unlike culture-based methods, technologies such as mass spectrometry and nucleic acid sequencing provide rapid and sensitive tools to probe the microbiome in clinical patients ( 39 )—as recently described for the ocular surface of veterinary species ( 40 , 41 )—enabling clinicians to optimize the antibiotic treatment sooner and thereby improve clinical outcomes ( 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…Among different species of the genus, the most predominantly involved in ocular diseases seems to be S. intermedius , followed by S. aureus and less coagulase negative staphylococci [ 18 ]. Although the second-most detected genus in this study was Trueperella , other studies have suggested a minor involvement in the pathogenesis of ocular diseases [ 19 , 20 ]. Conversely, the genus Micrococcus seems to be detected from both normal and pathogenic flora [ 20 , 21 , 22 ].…”
Section: Discussionmentioning
confidence: 55%
“…However, a decrease in positive fungal cultures were found after 2 weeks of NPB in normal horses ( 13 ). Additionally, in both normal dogs and horses, 1 week of NPB treatment did not significantly disrupt major bacterial taxa as measured by next generation sequencing ( 30 , 31 ). Conversely, in dogs, topical ofloxacin for 3 weeks after cataract surgery has been shown to lead to a decrease in positive bacterial cultures during treatment, an increase in positive bacterial cultures 3 weeks after stopping treatment, and an alteration in bacterial sensitivity ( 32 ).…”
Section: Discussionmentioning
confidence: 95%